Police Prosecutions and Punitive Instincts - Kate Levine (Washington University Law Review, 2021)
This Article makes two contributions to the fields of policing and criminal legal scholarship. First, it sounds a cautionary note about the use of individual prosecutions to remedy police brutality. It argues that the calls for ways to ease the path to more police prosecutions from legal scholars, reformers, and advocates who, at the same time, advocate for a dramatic reduction of the criminal legal system’s footprint, are deeply problematic. It shows that police prosecutions legitimize the criminal legal system while at the same time displaying the same racism and ineffectiveness that have been shown to pervade our prison-backed criminal machinery. The Article looks at three recent trials and convictions of police officers of color, Peter Liang, Mohammed Noor, and Nouman Raja, in order to underscore the argument that the criminal legal system’s race problems are playing themselves out predictably against police officers. The Article argues that we should take the recent swell of prison abolitionist scholarship to heart when we look at police prosecutions and adds to that literature by exploring this controversial set of defendants that are considered a third rail, even among most abolitionists. Second, the Article argues that police prosecutions hamper large-scale changes to policing. By allowing law enforcement to claim that brutality is an aberration, solvable through use of the very system that encourages brutality in the first place, we re-inscribe the failures of policing and ignore the everyday systemic and destructive violence perpetrated by police on communities of color. In order to achieve racial justice and real police reform, we must reduce our reliance on the police, rather than looking to the criminal legal system to solve this crisis.
Keywords: Criminal law; Police prosecutions; Prison abolition; Police reform; Race and the law; Police brutality